Haloflavibacter putidus gen. nov., sp. nov., isolated from coastal seawater. Issue 6 (22nd June 2020) - Feng, Xi; Wang, Yi-Ran; Zou, Qi-Hang; Zhang, Jin-Yu; Du, Zong-Jun
Abstract : A Gram-stain-negative, aerobic, gliding, rod-shaped (0.2–0.5×1.0-13.0 µm) and yellow-pigmented bacterium, designated PLHSN227 T, was isolated from seawater collected near the coast of Yantai, PR China. PLHSN227 T was found to grow at 15–37 °C (optimum, 28–30 °C) and pH 6.0–8.5 (optimum, 6.5–7.5) in the presence of 2–14 % (w/v) NaCl (optimum, 5.0 %). Phylogenetic analysis of the 16S rRNA gene sequences revealed that PLHSN227 T represented a member of the family Flavobacteriaceae and exhibited the highest sequence similarity (94.6 %) to the type strain Salegentibacter holothuriorum NBRC 100249 T . The chemotaxonomic analysis revealed that the sole respiratory quinone was menaquinone 6 (MK-6) and the major fatty acids included C19 : 0 ω8 c cyclo, iso-C15 : 0, anteiso-C15 : 0, C18 : 0 and summed feature 8 (C18 : 1 ω7 c and/or C18 : 1 ω6 c ). The major polar lipids included phosphatidylethanolamine, one unidentified aminolipid and two unidentified lipids. The DNA G+C content of PLHSN227 T was 35.6 mol%. PLHSN227 T showed the highest average amino acid identity value of 67.2 %, the average nucleotide identity value of 75.6 and 14.5 % digital DNA–DNA hybridization identity with Mesonia algae DSM 15361 T . According to the phylogenetic data, PLHSN227 T formed a distinct clade in the phylogenetic tree. On the basis of phenotypic, chemotaxonomic and phylogenetic data, it is considered that PLHSN227 T represents a novel genus within the family Flavobacteriaceae, for which the name Haloflavibacter putidus gen. nov., sp. nov. is proposed. The type strain is PLHSN227 T (=KCTC 72159 T =MCCC 1H00371 T ).